Laporan Proyek Akhir Pengukur Tinggi Badan Dengan Output suara Berbasis Arduino Mega Menggunakan Sensor Ultrasonik HC-SR04 - FARZI, Abizar ([Yogyakarta] : Universitas Gadjah Mada, 2014)
At the time of this technology to design an aid man many activities in life that is automatic . Devices used equipment among other miscellaneous electronic equipment and electrical , thermodynamic , hydraulic and others. Where the consideration is taken to designing such a device is in terms of comfort and safety of humans as users of such tools and the development in all fields of technology . Based on the above phenomenon industries engaged in all fields of technology resulted in a tool that is Arduino Microcontroller . Arduino is an electronic kit or open-source electronic circuit board in which there is a major component of which is a microcontroller chip with the type of company Atmel AVR . The microcontroller itself is a chip or IC ( integrated circuit) that can be programmed using a computer. So microcontroller served as the ' brain ' that controls the input , process and output of an electronic circuit . Microcontroller exist in electronic devices around us . For example mobile phones , MP3 players , DVD , television , air conditioning , etc. . The purpose of this study is to design a height gauge with Arduino Mega -based voice output using HC - SR04 ultrasonic sensor . Have done the design and realization of gauge height in centimeter scale with voice output . This tool can be used as an alternative in the measurement of human height is effective and efficient . The instrument hardware consists of an Arduino Mega , HC - SR04 sensor , LCD , modules SD CARD , and speakers . This tool works like a regular height gauges that measure the scale height in centimeters . When the height is measured by how high a person or object in the reduce the actual distance to get the result in the actual height measurement then the calculation result data will be processed by the microcontroller to display the output sound . This tool has been realized and can measure height in centimeter scale with the sound output.